PENDAYAGUNAAN POTENSI DESA MELALUI PELATIHAN PEMBUATAN SERBUK MINUMAN JAKA (JAHE DAN KAPULAGA) DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT - Muhamamd Isa Anshory; Galang Ijtihadul Ulama; Istiqomatul Maftukhah; Wahyu Intan Kusuma; Fidiyatus Solikhah; Dian Ayu Pratiwi (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
One of the areas in Pekalongan Regency, precisely in the mountainous part, which has great potential in the agricultural sector, is Tembelanggunung Village. With its natural riches such as sugar palm, reeds, cardamom, ginger, and others. Empowerment activities through the use of existing materials to develop potential. The main aim is to increase community skills in the JAKA process. Both practical and theoretical training can be provided, especially in the form of technical knowledge and skills regarding JAKA preparation. The empowerment scheme is carried out by providing 1 package of assistance (Ginger, Cardamom, Lemongrass, Pandan Leaves, Sugar) through this group. Through this activity, the community feels a change in the form of increasing knowledge, and community income can increase